Performance of lambs fed diets with different concentration of Prosopis laevigata pods - Mejia Haro, Ignacio (Acta Universitaria, 2021)
The objective of the study was to evaluate the effects on performance and products of ruminal fermentation of lamb diets in a sheep trial composed of 18 male lambs distributed randomly in three treatment diets containing different concentration of ground mesquite pods (VMM): 0% VMM (T1), 15% VMM (T2), and 30% VMM (T3). The nutritional composition of VMM and diets was determined. Feed intake, weight gain, and feed conversion were measured. In rumen, Volatile Fatty Acids (VFA) and N-NH3 were evaluated. Weight gain, feed intake, and feed conversion were similar (p > 0.05) among treatments, as well as the production of VFA and N-NH3 (p > 0.05). The mesquite pods provide an adequate nutritional content to be used in lamb diets without affecting the performance when used in 15% or 30%.